2018
DOI: 10.22606/gr.2018.33001
|View full text |Cite
|
Sign up to set email alerts
|

Landslide Disaster Risk Reduction Strategies and Present Achievements in Sri Lanka

Abstract: Abstract. A significant impact on the economy and the social context of Sri Lanka has been caused by hydro-meteorologically induced landslides. Though many organizations are working on landslide studies, National Building Research Organization (NBRO) is the key organization that involves in landslide research and risk reduction programs in Sri Lanka. This paper discusses about the present strategies set to reduce the landslide risk and the present achievements. Landslide risk reduction process has been strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…e National Building Research Organization (NBRO) has declared 14 districts, which constitute one-third of the land in Sri Lanka, as landslide vulnerable areas [3]. Studies conducted by the NBRO have revealed that nearly 70% of the landslides that occurred in populated areas in Sri Lanka are human-induced [4]. As a result, the frequency and severity of landslides in the country have increased in the recent past, which is in line with global trends [5][6][7].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…e National Building Research Organization (NBRO) has declared 14 districts, which constitute one-third of the land in Sri Lanka, as landslide vulnerable areas [3]. Studies conducted by the NBRO have revealed that nearly 70% of the landslides that occurred in populated areas in Sri Lanka are human-induced [4]. As a result, the frequency and severity of landslides in the country have increased in the recent past, which is in line with global trends [5][6][7].…”
Section: Introductionmentioning
confidence: 75%
“…While this database focuses on recording information about landslides, it does not contribute to predisaster planning and preparedness. As a developing country, Sri Lanka needs a comprehensive landslide inventory that includes the capacity to support predisaster planning and preparedness, hazard assessment, disaster risk mitigation, risk management, and contingency planning [4].…”
Section: Introductionmentioning
confidence: 99%
“…The Colombo-Kandy railway track, which connects to other major cities located to the southeast of Kandy and in the hill country, also runs close to the highway at Kadugannawa. Landslides and slope failures have occurred frequently in the Kadugannawa area, causing significant damage in 2003, 2016 [31], and 2021 (the most recent failure). This may be attributed to the intense rainfall in recent years and the encroachment of dwellers and residences along the roadside with the aim of selling items to passengers and providing easy transportation for them.…”
Section: Introductionmentioning
confidence: 99%
“…The 2.6 km long historical wall, one of the inherited heritage sites in the Volterra (Central Italy) settlement, has suffered a significant amount of structural damage due to the disrupted slope stability that is caused by both the geological conditions and technical operation for facilitating uncontrolled settlement (Teresa et al 2016) [2]. Bandara and Jayasingha (2018) [3] state that in Sri Lanka, which is one of the rapidly growing cities, there is a linear relationship between the increase in the urban population and the increase in the number of landslides. In the said region, the settlement strategies are regulated by NBRO (National Building Research Organization) since 1994.…”
Section: Introductionmentioning
confidence: 99%